Trends in incidence, mortality, and DALYs of cystic echinococcosis in Central Asia from 1992 to 2021: an age-period-cohort analysis - Talafuhan, Wulan; Tuoheti, Kaibinuer; Lixia, Ye; Shuang, Qi; Yeerjiang, Mieyier; Aizezi, Guzalinuer; Jingjing, Wei; Mijiti, Peierdun (Frontiers in Public Health, 2025)
BackgroundCystic echinococcosis (CE) is widespread globally but imposes a particularly heavy burden in Central Asia. Despite control measures, disease management remains suboptimal in this region. This study analyzed trends in CE incidence, mortality, and disability-adjusted life years (DALYs) from 1992 to 2021 in Central Asia; compared them with global data; and explored variations by gender, age group, and country to identify critical factors in disease control.MethodsUsing data from the Global Burden of Disease Study 2021 (GBD 2021), we analyzed long-term trends in the incidence, mortality, and DALY rates of CE in Central Asia. The joinpoint regression model was employed to calculate the annual percentage change (APC) and average APC (AAPC) to identify shifts in disease trends. Additionally, an age-period-cohort model was used to assess the impact of various age groups, periods, and birth cohorts on the disease burden.ResultsThe number of CE cases increased by 52.13% in Central Asia, while deaths decreased by 57.35%; DALYs decreased only slightly by 10.75%. From 1992 to 2021, CE incidence showed an increasing trend until 2010, then rapidly declined until 2015, and then gradually increased thereafter. The highest incidence rates were among middle-aged and older adult populations. Although mortality and DALY rates decreased across all age groups, the decline was less than the global trend. Gender analysis showed that the incidence rate was significantly higher in males than in females.ConclusionAlthough there have been improvements in the CE disease burden in some Central Asian countries, the overall burden remains significant. This study highlights the importance of considering gender, age, and country-specific disease burdens when formulating public health policies. Future research should continue to monitor these trends and explore targeted prevention strategies within diverse socioeconomic contexts, such as integrating regional socioeconomic factors and public health resources.